Some methods for competing risks with and without masked cause of failure: a short review - Yosra , Yousif; Elfaki, Faiz Ahmed Mohamed; Meftah, Hrairi; Azram, Mohammad (Sci.Int.(Lahore), 2015)
Standard survival analysis focuses on failure-time data that has one type of failure. Competing risks arise in studies when subjects are exposed to more than one cause of failure and failure due to one cause excludes failure due to other causes. Examples of competing risks data can be found in many fields such as public health, industrial reliability, and demography. In some circumstances, the cause of failure in competing risks data could be masked. In such situations the standard survival analysis might not be applicable. There has been considerable work done discussing these issues in the statistical literature during the past several years, and this paper presents a review of some methods proposed for competing risks data with and without masking.